Assessing the footprint and volume of oil deposited in deep-sea sediments following the Deepwater Horizon oil spill. Issue 1 (15th January 2017) - Stout, Scott A.; Rouhani, Shahrokh; Liu, Bo; Oehrig, Jacob; Ricker, Robert W.; Baker, Gregory; Lewis, Christopher
Abstract: The lateral and vertical extents of Macondo oil in deep-sea sediments resulting from the 2010 Deepwater Horizon oil spill were determined using chemical forensics and geostatistical kriging of data from 2397 sediment samples from 875 cores collected in 2010/2011 and 2014. The total mass of Macondo-derived hopane on the seafloor in 2010/2011 was conservatively estimated between 2.00 and 2.26 metric tons, derived from 219, 000 to 247, 000 barrels of oil; or 6.9 to 7.7% of the 3.19 million barrels spilled. Macondo-derived hopane was deposited over 1030 to 1910 km 2 of the seafloor, mostly (> 97%) in surface (0–1 cm) and near-surface (1–3 cm) sediments, which is consistent with short-term oil deposition. Although Macondo oil was still present in surface sediments in 2014, the total mass of Macondo-derived hopane was significantly lower (~ 80 to 90%) than in 2010/2011, affirming an acute impact from the spill and not long-term deposition from natural seeps.